2018
DOI: 10.1101/435933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New insights into the ORF2 capsid protein, a key player of the hepatitis E virus lifecycle

Abstract: Importance 46Hepatitis E virus (HEV) infection is the most common cause of acute viral hepatitis 47 worldwide. This infection can become chronic in immunosuppressed patients and cause death 48 in some patients. In our study, we focused on ORF2 viral capsid protein for which we 49 recently identified glycosylated and non-glycosylated forms. The non-glycosylated form, 50 named ORF2i, is the form associated with the infectious particles. The glycosylated forms, 51 named ORF2g and ORF2c, are the major antigens pre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…We and others previously showed that the ORF2 protein is translocated into the nucleus of infected cells of patient liver biopsies 14 and in cell culture system 12 . Here, we first analyzed the ORF2 expression in PLC3 cells electroporated with the infectious p6 strain (PLC3/HEV-p6), at different time postelectroporation (p.e.)…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…We and others previously showed that the ORF2 protein is translocated into the nucleus of infected cells of patient liver biopsies 14 and in cell culture system 12 . Here, we first analyzed the ORF2 expression in PLC3 cells electroporated with the infectious p6 strain (PLC3/HEV-p6), at different time postelectroporation (p.e.)…”
Section: Resultsmentioning
confidence: 89%
“…It is not glycosylated and is likely derived from the assembly of the intracellular ORF2 (ORF2intra) form present in the cytosolic compartment. Importantly, we showed that a fraction of the ORF2intra form is translocated into the nucleus of infected cells 12 . In contrast, ORF2g and ORF2c proteins (herein referred to as ORF2g/c) are highly glycosylated and secreted in large amounts in culture supernatant (i.e., about 1000x more than ORF2i 13 ) and are the most abundant antigens detected in patient sera 11 .…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Comparing the virologic parameters in the stool and the plasma of the infected mice revealed high HEV RNA content in the stool compared with the plasma, while HEV ORF2Ag showed an inverse correlation. Stool-derived HEV particles were more infectious than plasma-derived HEV, when they were passaged into naïve mice 65,73 Humanized mice were used to characterize the infectivity of the fraction (fraction 6) of HEVcc that includes only ORF2i. Unlike the HEVcc supernatant, fraction 6 was infectious to the mice indicating that the removal of noninfectious ORF2 Ag increased the infectivity of the HEV preparation, probably due to absence of competitive binding between both infectious and noninfectious ORF2 Ag to the receptor.…”
Section: Use Of Humanized Mice For Characterization Of Hev Particlementioning
confidence: 99%
“…ORF2g along with a cleaved form of ORF2 Ag (ORF2c) were the major Ags detected in patient serum, indicating that the HEV Ag ELISA assay (HEV-Ag ELISA Plus assay (Bejing Wantai Biological Pharmaceutical) could detect both infectious and noninfectious ORF2 Ag. 65,73 Therefore, the ELISA Ag assay data should be interpreted cautiously, since this assay might not necessarily detect an active infection.…”
Section: Kinetics Of Hev Orf2 Ag During the Course Of Hev Infectionmentioning
confidence: 99%